Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Muna Barat - Nurwati Nurwati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This research aims to test and explain the simultaneous and partial influence of workload and work environment on the performance of employees of the Secretariat of the Regional People's Representative Council (DPRD) of West Muna Regency. This research approach is a survey with an explanatory research design. The sample for this research was employees and honorary staff of the Secretariat of the Regional People's Representative Council (DPRD) of West Muna Regency using a purposive sampling method of 41 people. The data collection method uses a questionnaire. The analysis equipment used is multiple linear regression. The research results show that simultaneously workload and work environment have a positive and significant effect on employee performance at the Secretariat of the Regional People's Representative Council (DPRD) of West Muna Regency. Partially, workload has a negative and insignificant effect on employee performance, while the work environment has a positive and significant effect on employee performance. Thus, it can be concluded that workload does not have a positive and significant contribution to employee performance, while the work environment has a positive contribution to increasing employee performance which is described through quality, quantity, punctuality, attendance and ability to work together.